WAVEGUIDE ANTENNA PROPOSAL WITH RESONANT SLOTS FOR WLAN APPLICATIONS - Bethart Rodríguez, Nayrebis; Cordoví Rodríguez, Tuan Ernesto; Jiménez Hernández, Roberto; Beltrán Casanova, David (Telemática, 2020)
The Slotted Waveguide Antenna (SAW) are chosen as very economical antennas because they have high relative gain values and a structure with little complexity. Therefore, the present work is aimed at the design and manufacture of a type of slotted waveguide antenna for Wi-Fi wireless network applications to satisfy the needs existing by customers who wish to connect entities through network connection wireless fundamentally in the 2.4 GHz band. Due to the new technological changes in which the Cuban Telecommunications Company (ETECSA) is immersed, it raises the need for import substitution with their development. To fulfill the purpose of this work, several documents were analyzed with which the characteristics of the grooved waveguide antennas could be studied where there is no clarity about the design methodology. That is why we start with the proposal of an antenna design methodology. With the support of a 3D modeling and electromagnetic simulation software, the typical parameters within the operating frequency band are obtained. Finally, the experimental results obtained in the measurements made to various prototypes of antennas are provided for validation.